Fenomena Tradisi Ziarah Lokal dalam Masyarakat Jawa: Kontestasi Kesalehan, Identitas Keagamaan dan Komersial - M Misbahul Mujib (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2016)
This study discusses the grave pilgrimage traditions that have long made the Java community in particular through a phenomenological approach with increasing pilgrim graves in 1 the last decade, although the level of jurisprudence still reap the pros and cons. The study revealed several factors causing the increase in the grave pilgrims. The survey results revealed that there are many aspects that influence the increased pilgrim grave. In addition, the grave pilgrimage as a tradition that has existed since before Islam, it’s recognized that it has aspect of religious ritual worship (piety) with the normative arguments as an amplifier. Efforts of pilgrims who actually aimed at showing religious identity or religious symbols as the persistence of the abangan are still not understood in the perspective of religious pilgrimage and the orthodox clergy who rejected the implementation of the pilgrimage also affect many pilgrims. Another dimension is an important factor increasing the pilgrims grave is none other than the commercial factor, because many pilgrims could significantly increase the economic level of the community around the shrine grave, grave pilgrimage organizers and it can even be a source of local revenue. So that the improvement of infra structure grave shrine is also an important factor increasing the grave pilgrims.